Peran Pancasila dalam Membentuk Karakter Mahasiswa Program Studi Pendidikan Vokasional Kesejahteraan Keluarga Universitas PGRI Adi Buana Surabaya - Afiatun Nafiah; Yuliana Safitri; Izza Milla Syarifa; Nurul Qodheriyah; Zanuar Khofifah; Intan Seriana Naingolan; Chintya Dwi Anggraini; Wisnu Djati Vardhana; Suyono Suyono (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Pancasila education in higher education has an important role in shaping noble moral character among students. By understanding and applying the values of Pancasila, it is hoped that students can develop strong character, responsibility, and integrity. The purpose of the research is to gain an in-depth understanding of the role of Pancasila education in shaping student character and building solid morals. This research is qualitative research through literature. Literature collection by collecting relevant sources such as scientific journals, books, articles and other relevant documents. The main source of this research is scientific articles published on Google Scholar. Data analysis is carried out qualitatively which includes data reduction, data presentation, and conclusion drawn. The results of data analysis show that Pancasila education does need to be used as a foundation to develop strong ethics and morals, where activities in the university environment include habits that can encourage students to behave according to behavior based on Pancasila values.